The Influence of the Self-Directed Learning Approach on the Independence and Learning Outcomes of Grade 10 Students at SMAN 2 Bulukumba in Mathematics Learning - Rahman, Abdul; Sutamrin, Sutamrin; Syakir, Ade Irma Zetyani (ARRUS Journal of Mathematics and Applied Science, 2024)
This research aims to determine the influence of the Self-Directed Learning approach on the independence and learning outcomes of grade 10 students at SMAN 2 Bulukumba in mathematics learning. This research is a pre-experimental study using a one-group pre-test-post-test method. The population in this study was all grade 10 students at SMAN 2 Bulukumba, consisting of 10 classes, and the sample of this study was class X.1 with 28 students. Data was collected using learning outcome tests and learning independence questionnaires. The data analysis technique used was descriptive and inferential statistical analysis. The results of the descriptive statistical analysis are: (1) The average score of students' learning outcomes before the implementation of the Self-Directed Learning approach was 25.78, which is categorized as very low, (2) The average score of learning outcomes after the implementation of the Self-Directed Learning approach was 81.40, which means it is in the high category, (3) students' learning independence before the implementation of the Self-Directed Learning approach before the implementation of the Self-Directed Learning approach was in the fairly independent category or with an average score of 46.16, (4) students' learning independence after the implementation of the Self-Directed Learning approach was in the independent category or with an average score of 64.49. Meanwhile, the results of inferential statistical analysis show that the implementation of the Self- Directed Learning approach has a positive impact on the learning outcomes and learning independence of grade 10 students at SMAN 2 Bulukumba.